FRASA NOMINA PADA SISTIM BAHASA ANTAR SISWA SMA MUHAMMADIYAH II SURAKARTA - Fauziati, Endang (Widya Wacana: Jurnal Ilmiah, 2016)
The English of Senior High Schhol students in Indonesia is quite interesting to studybecause it contanis a significant number of errors, especially in the writing of a noun phrase.This phenomenon shows that the English used contains Interlanguage. Selinker states thatInterlanguage has its own linguistic system. This study aims to describe and explain thelinguistic system of noun phrase in the leaners’ interlanguage as well as factors that contributeto the formation of the noun phrase. The subjects of this study were 40 students of SMAMuhammadiyah Surakarta II Class X. The data were collected through elicitation technique, thestudents were asked to write free composition. Data were analyzed using framework of erroranalysis which includes four stages: elicitation, identification, description and explanation orinterpretation. The results of the data analysis indicate seven noun phrase patterns as follows:(1) the use of mother tongue (Indonesian), (2) the use of combination of Indonesian and English,(3) the use of cognate, (4) the use of the Arabic already naturalized into Indonesian, (5) theexistence of miscollocation, (6) the use of false friend, and (7) the use of infinitive verbs insteadof Verb-ing. With regards to factors that contribute to the formation of the noun phrase, theresults show that these are due to the following factors: (1) muilingualism of the Englishlearners, (2) the gap between the Indonesian vocabulary repertoire and English, (3) theutilization of the previous lerned languages (Indonesia, Arabic) in their English expressions,and (4) the lack of control of the structure of the English noun phrase.Keywords: noun phrases, noun phrase patterns, factors which contribute to the formation ofnoun phrases